Alterations in vasomotor systems and mechanics of resistance-sized mesenteric arteries from SHR and WKY male rats following in vivo testosterone manipulation - Toot, Jonathan D (BioMed Central, 2012)
BACKGROUND: Testosterone (T) and the sympathetic nervous system each contribute to the pathology of hypertension. Altered blood vessel reactivity is also associated with the pathology of high blood pressure. The purpose of this study was to examine the effects of T manipulation in the regulation of resistance-sized blood vessel reactivity. METHODS: Adult spontaneously hypertensive (SHR) and Wistar Kyoto (WKY) male rats at 8 weeks of age were used. The rats were divided into groups consisting of gonadally intact controls (CONT), castrate with sham implant (CAST) and castrate with T implant (CAST + T) (n = 6 to 12 per group). Following a short-term period of T treatment (approximately 4 weeks), plasma norepinephrine (NE) and plasma T were assessed by performing high-performance liquid chromatography and RIA, respectively. Resistance-sized mesenteric artery reactivity was assessed on a pressurized arteriograph for myogenic reactivity (MYO), phenylephrine (PE) responsiveness and passive structural mechanics. RESULTS: SHR and WKY males exhibited similar physiological trends in T manipulation, with castration significantly lowering plasma T and NE and T replacement significantly increasing plasma T and NE. T manipulation in general resulted in significant alterations in MYO of second-order mesenteric arteries, with T replacement decreasing MYO in SHR (P < 0.05) compared to CONT, T replacement increasing MYO, and CAST decreasing MYO in WKY rats (P < 0.001) compared to CONT rats. Additionally, PE-induced constriction was significantly altered in both strains following T treatment, with the effective concentration of PE to constrict the vessel to 50% of the total diameter significantly increased in the CAST + T SHR compared to CONT (P < 0.05). Comparisons of passive structural mechanics between SHR and WKY treatment groups indicated in SHR a significantly increased wall-to-lumen ratio and decreased circumferential wall stress compared to WKY treatment groups. CONCLUSIONS: These data suggest that T and NE are involved in a complex interaction with both myogenic reactivity and structural alterations of resistance-sized blood vessels and that these factors likely contribute to the development and maintenance of hypertension.